ASSESSING THE EFFICACY OF TWO SEVERITY SCORING SYSTEMS IN PREDICTING PROGNOSIS FOR ACUTE KIDNEY FAILURE, BHAGALPUR: A COHORT STUDY. - Anand, Ravi; Bhushan, Sneha (Student’s Journal of Health Research Africa, 2024)
Background Acute kidney failure (AKI) causes waste buildup and fluid-electrolyte imbalances due to rapid renal function loss, necessitating accurate outcome prediction using APACHE II and SOFA scores due to its high morbidity and death. The study aims to compare the predictive accuracy of the SAPS 3 and APACHE IV severity scoring systems in forecasting mortality among patients with AKI admitted to the intensive care unit (ICU). Methods The cohort study involves 150 AKI ICU patients. Detailed medical histories, systemic exams, and pertinent blood testing were collected. SAPS 3 and APACHE IV scores were determined within one hour and 24 hours of ICU admission, respectively. Mortality rates were predicted using calculators. SPSS 20 was used for statistical analysis. Results The study comprised 150 patients with an average age of 58 years; 65% were male. Common co-morbidities were hypertension (42%), diabetes mellitus (28%), and cardiovascular disease (18%). Mean SAPS 3 and APACHE IV scores were 52 and 46, respectively. Predicted mortality rates were 30% (SAPS 3) and 28% (APACHE IV), with an observed mortality of 30%. Deceased patients had higher mean scores (SAPS 3: 62, APACHE IV: 58). ROC analysis showed AUCs of 0.85 for SAPS 3 and 0.82 for APACHE IV. Sensitivity and specificity were 76% and 82% (SAPS 3), and 72% and 79% (APACHE IV). Both scores were considerably related to mortality (p < 0.001). Conclusion Both SAPS 3 and APACHE IV scoring systems demonstrated good predictive accuracy for mortality in AKI individuals admitted to the ICU, with no significant difference in their performance. Recommendations Further research should explore integrating machine learning algorithms and additional biomarkers to enhance the predictive accuracy of these scoring systems. Continuous evaluation and refinement are essential to improve their utility in clinical practice.